The association of dental plaque with cancer mortality in Sweden. A longitudinal study. Issue 3 (11th June 2012) - Söder, Birgitta; Yakob, Maha; Meurman, Jukka H; Andersson, Leif C; Söder, Per-Östen
Abstract : Objectives: To study whether the amount of dental plaque, which indicates poor oral hygiene and is potential source of oral infections, associates with premature death from cancer. Design: Prospective cohort study. Participants: 1390 randomly selected healthy young Swedes followed up from 1985 to 2009. All subjects underwent oral clinical examination and answered a questionnaire assessing background variables such as socioeconomic status and smoking. Outcome measures: Causes of death were recorded from national statistics and classified according to the WHO International Classification of Diseases. Unpaired t test, χ 2 tests and multiple logistic regressions were used. Results: Of the 1390 participants, 4.2% had died during the follow-up. Women had died at a mean age of 61.0 (±2.6 SD) years and men at the age of 60.2 (±2.9 SD) years. The amount of dental plaque between those who had died versus survived was statistically significant (p<0.001). In multiple logistic regression analysis, dental plaque appeared to be a significant independent predictor associated with 1.79 times the OR of death (p<0.05). Age increased the risk with an OR of 1.98 (p<0.05) and gender (men) with an OR of 1.91 (p<0.05). The malignancies were more widely scattered in men, while breast cancer was the most frequent cause of death in women. Conclusions: This study hypothesis was confirmed by showing that poor oral hygiene, as reflected in the amount of dental plaque, was associated with increased cancer mortality.